2016
DOI: 10.1371/journal.pgen.1005679
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Genomic Analysis Reveals the Genetic Landscape of Mitochondrial Respiratory Chain Complex Deficiencies

Abstract: Mitochondrial disorders have the highest incidence among congenital metabolic disorders characterized by biochemical respiratory chain complex deficiencies. It occurs at a rate of 1 in 5,000 births, and has phenotypic and genetic heterogeneity. Mutations in about 1,500 nuclear encoded mitochondrial proteins may cause mitochondrial dysfunction of energy production and mitochondrial disorders. More than 250 genes that cause mitochondrial disorders have been reported to date. However exact genetic diagnosis for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
279
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(307 citation statements)
references
References 70 publications
10
279
1
Order By: Relevance
“…To date, 26 patients are reported with LTBL (12 by Steenweg et al (2012), one by Talim et al (2013), two by Taylor et al (2014), one by Biancheri et al (2015), one by Kohda et al (2016), one by Kevelam et al (2016), one by Danhauser et al (2016), one by Taskin et al (2016), one by G€ ung€ or et al (2016), two by Şahin et al (2016) and two by Pronicka et al (2016)), with our patient being the 26th reported patient. The phenotype of our patient fits the severe group of LTBL patients, mostly due to signs of perinatal presentation of the disease and rapid decline of her clinical status.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…To date, 26 patients are reported with LTBL (12 by Steenweg et al (2012), one by Talim et al (2013), two by Taylor et al (2014), one by Biancheri et al (2015), one by Kohda et al (2016), one by Kevelam et al (2016), one by Danhauser et al (2016), one by Taskin et al (2016), one by G€ ung€ or et al (2016), two by Şahin et al (2016) and two by Pronicka et al (2016)), with our patient being the 26th reported patient. The phenotype of our patient fits the severe group of LTBL patients, mostly due to signs of perinatal presentation of the disease and rapid decline of her clinical status.…”
Section: Discussionmentioning
confidence: 61%
“…The fifth patient from Taskin et al (2016) had a homozygous c.322C>T (p.Arg108Trp) missense change and presented a mild phenotype. Compound heterozygous changes were identified in three additional patients as part of large-scale WES studies but without specific details of phenotypes for comparison (Kohda et al 2016;Pronicka et al 2016). Regarding the two heterozygous variants in our patient, the start-loss p.Met1?…”
Section: Discussionmentioning
confidence: 97%
“…Mutations affecting mitochondrial translation machinery have often been associated with liver dysfunction. 8,11,58 The observed differences in presentation between individual patients and the mouse model may reflect the importance of both the location and severity of the mutation (including hypomorphic versus loss-of-function alleles) as well as the genetic background. This consideration is also relevant to the observed differences in both onset and progression of clinical disease between the different MRPS34 human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…14 Disorders caused by mutations in mitoribosomal proteins are clinically heterogeneous and multi-systemic, with common features including neurodevelopmental disabilities, brain abnormalities, liver disease, kidney disease, cardiomyopathy, and lactic acidosis. 11,15 They generally lead to death in infancy or early childhood, 15 although survival into teenage years and adulthood has been reported. 8,14,16 The small number of mitoribosomal genes known to underlie OXPHOS diseases is surprising, since nearly two-thirds of mitoribosomal genes are essential for OXPHOS based on a highthroughput knock-out death screen in cell models.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of disorders of CIII-deficiency is challenging as they comprise a group of rare conditions that have vastly different phenotypes. The advent of whole-exome sequencing has also facilitated the molecular diagnosis of these rare disorders (Kohda et al 2016).…”
Section: Introductionmentioning
confidence: 99%